Reason, Love, and Morality The Limits of Reason in Kohlberg and the Importance of Love in Augustine and Smith - Sosler, Alex (2019)
This study contrasts the moral development theory of Lawrence Kohlberg with the Augustinian structure represented in the work of James K. A. Smith. Where Kohlberg emphasizes cognition and rational ability, Smith focuses on the formation of loves acquired by habits. The theories differ ontologically and teleologically, which results in wide pedagogical distinctions. This study suggests that focusing on the loves through formation offers a richer expression of education and a more holistic forming of students